THE EFFECT OF CUSTOMER PARTICIPATION ON CO-CREATION OUTCOME OF ONLINE TRANSPORTATION IN MANADO - Lumempouw, Maureen B. K.; Massie, James D. D.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2019)
Abstract: The significant growth of internet and smartphone users, affecting the development of e-commerce businesses in Indonesia. One of them is the online transportation business. Online transportation companies initiate a strategy to involve the end-users or customer in one or more stages of innovation, this strategy is Co-creation. The aim of this research is to analyze the effect of Customer Participation on Co-Creation Outcome of Online Transportation in Manado using Dimensions of Customer Participation (Information Seeking, Information Sharing, Responsible Behavior, Personal Interaction). The type of this research is a causal research and used quantitative research method. Population in this research is the people that have experienced of using online transportation. The sample size of this research is 100 respondents which are the customer of Gojek and Grab in Manado. This research found that The independent variable which are Information Seeking, Information Sharing, Responsible Behaviour and Personal Interaction simultaneously affect Co-Creation Outcome as the dependent variable. There are 3 independent variables; Information Seeking, Information Sharing and Responsible Behavior significantly affect Co-Creation Outcome. While there is one variable that does not have significant effect on Co-Creation Outcome which is Personal Interaction.Â Â Â Keywords: customer participation, co-creation outcome, online transportation